Antidepressant imipramine diminishes stress-induced inflammation in the periphery and central nervous system and related anxiety- and depressive- like behaviors - Ramírez Chan, Karol Gabriela (2016)
In order to relieve anxiety and depression accompanying stress, physicians resort to tricyclic antidepressants, such as imipramine. We had previously shown that imipramine reversed stress-induced social avoidance behavior, and down-regulated microglial activation 24 days after stress cessation. To further characterize the effects of imipramine on stress induced neuroimmune dysregulation and associated changes in behavior, the aims of this study were to determine if imipramine 1) ameliorated stress-induced inflammation in the periphery and central nervous system, and 2) prevented stress related anxiety- and depressive-like behaviors. C57BL/6 mice were treated with imipramine (15 mg/kg) in their drinking water, and exposed to repeated social defeat (RSD). Imipramine attenuated stress-induced corticosterone and IL-6 responses in plasma. Imipramine decreased the percentage of monocytes and granulocytes in the bone marrow and circulation. However, imipramine did not prevent splenomegaly, stress-related increased percentage of granulocytes in this organ, and the production of pro-inflammatory cytokines in the spleen, following RSD. Moreover, imipramine abrogated the accumulation of macrophages in the brain in mice exposed to RSD. Imipramine blocked neuroinflammatory signaling and prevented stress-related anxiety- and depressive-like behaviors. These data support the notion that pharmacomodulation of the monoaminergic system, besides exerting anxiolytic and antidepressant effects, may have therapeutic effects as a neuroimmunomodulator during stress.